THE INFLUENCE OF PRODUCT QUALITY PERCEPTIONS, BRAND IMAGE AND PRICE PERCEPTIONS ON PURCHASE INTEREST IN THE APPLE BRAND - Anggy Feby Yola Yukasih; Sri Setya Handayani; Resha Mahendra Razaq (Bisnis Manajemen dan Keuangan, 2024)
Apple is one of the large multinational companies in the technology field. Apple itself has innovated very well for the world of technology, especially satisfying consumer demand for its own products. This research aims to analyze and find out whether perceived product quality, brand image, and perceived price influence purchasing interest in the Apple brand. Data was collected by distributing questionnaires online with the help of Google Form services to 110 respondents. The analytical method used in this research is quantitative primary data with the testing tool used is SPSS. The test stages carried out were instrument testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, F test, t test, and coefficient of determination (KD) test. The sampling technique used was Purposive Sampling. The research results show that the variables of product quality perception, brand image, and price perception have a positive influence on purchase interest in the Apple brand.